New therapeutic targets and biomarkers for acute graft-versus-host disease (GVHD). (2nd September 2021) - Choe, Hannah; Ferrara, James L.M.
ABSTRACT: Introduction: Acute Graft-versus-Host Disease (GVHD) is the major toxicity of allogeneic hematopoietic cell transplantation (HCT). Systemic steroids are the standard primary treatment but only half of the patients will respond completely and the survival of steroid-refractory patients is poor. The gastrointestinal (GI) tract is a key target organ that usually determines a patient's response to therapy. Areas covered: This review summarizes the use of clinical grading systems and biomarkers in GVHD treatment and highlights pathophysiologic phases of acute GVHD as context for the mechanisms of action and therapeutic targets of various approaches. We reviewed >100 publications and performed a search of ongoing, current clinical trials on the emerging therapeutic targets for prophylaxis and treatment of acute GVHD. Search databases included clinicaltrials.gov and PUBMED. Search terms and keywords included 'acute graft-versus-host disease, ' 'GVHD, ' 'graft versus host, ' 'treatment.' Expert opinion: Future strategies will employ a risk-adapted therapy using biomarkers, which more accurately predict 6-month NRM. Strategies for high-risk patients will inhibit GI tract damage by selective targeting of effectors (e.g. inhibition of JAK signaling in T cells), blockade of trafficking through mAbs against integrin receptors, or enhancement of target cell survival. Future strategieswill reduce immunosuppression to avoid risk of infections and relapse.